2023
DOI: 10.1007/s11701-023-01691-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hospital consumption of opioid and non-opioid analgesics after colorectal endometriosis surgery

Adrien Crestani,
Amine Bibaoune,
Marjolaine Le Gac
et al.

Abstract: BackgroundThe aim of this study was to analyze postoperative consumption of analgesics during hospitalization following colorectal surgery for endometriosis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…The perioperative outcomes of our study revealed that there was no difference in blood loss or operative time between patients treated with RAL and those treated with CL; this finding coincides with what was reported by different researchers [21,26,31] [27,28,30,[32][33][34]]. An analysis of retrospective studies reported in recent years indicated a minimum operative time for RAL of 106 min [21] and the longest of 250 min [28], while for CL, the minimum time reported was 76 min [33], and the longest was 225 min [31].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The perioperative outcomes of our study revealed that there was no difference in blood loss or operative time between patients treated with RAL and those treated with CL; this finding coincides with what was reported by different researchers [21,26,31] [27,28,30,[32][33][34]]. An analysis of retrospective studies reported in recent years indicated a minimum operative time for RAL of 106 min [21] and the longest of 250 min [28], while for CL, the minimum time reported was 76 min [33], and the longest was 225 min [31].…”
Section: Discussionsupporting
confidence: 92%
“…The perioperative outcomes of our study revealed that there was no difference in blood loss or operative time between patients treated with RAL and those treated with CL; this finding coincides with what was reported by different researchers [21,26,31] [27,28,30,[32][33][34]]. An analysis of retrospective studies reported in recent years indicated a minimum operative time for RAL of 106 min [21] and the longest of 250 min [28], while for CL, the minimum time reported was 76 min [33], and the longest was 225 min [31]. Our results showed times considered within these ranges.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation